Prevalence and geospatial distribution of bovine cysticercosis in the state of Mato Grosso, Brazil - Rossi, Gabriel Augusto Marques [UNESP]; de Simoni, Heloisa Adélia Stefanoni; Lopes, Welber Daniel Zanetti; Almeida, Henrique Meiroz de Souza [UNESP]; Soares, Vando Edésio; Vidal, Ana Maria Centola; Ferraudo, Antonio Sergio [UNESP]; Mathias, Luis Antonio [UNESP] (Elsevier, 2016)
This study focused on estimating the prevalence and evaluating the geospatial distribution of bovine cysticercosis in the state of Mato Grosso, Brazil. To this, we used data of 6,200,497 animals slaughtered during the years of 2013 and 2014, and from 141 municipalities of the state. The prevalence observed for this period was 0.0873% (95% CI 0.0851–0.0897). Regarding the cysticerci detected, the calcified ones were the most frequent (74.43%). The high odds ratios were observed in animals reared in the Administrative Regions of Sinop, Barra do Garças, Água Boa, Cáceres, Barra do Bugres, Cuiabá, Pontes Lacerda, Rondonópolis, Matupa, São Félix do Araguaia and Lucas do Rio Verde, respectively. Furthermore, the results indicate the existence of a relation between the areas with high cysticercosis prevalence and human population density. We highlight the need of the development of a risk model based on the origin to improve cysticercosis detection in endemic areas.
Keywords: Cattle meat inspection; Geographic information system (GIS); Taenia saginata; Zoonosis